2021
DOI: 10.1021/acsomega.1c02045
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Kelvin Resolution at Room Temperature Using Nanomechanical Thermometry

Abstract: Ultrahigh sensitivity temperature measurement is becoming increasingly relevant for different scientific and technological fields from fundamental physics to high-precision engineering applications. Here, we demonstrate the use of a nanomechanical resonator—free standing silicon nitride membranes with thicknesses in the nanoscale—for room temperature thermometry reaching an unprecedented resolution of 15 μK. These devices were characterized by using an interferometric system at high vacuum, where there are onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous works on interferometric studies of membrane NMRs demonstrate not only imperfections in the amplitude mode shape [ 51 ], but also variations of with laser beam spot position in the presence of metallic nanoparticles [ 52 ]. A localized laser heating study on membranes made from silicon nitride [ 53 ] suggests that the spot location should be accounted for when performing power-dependent bolometric tests because applying high would induce radial dependence of the measured . Figure S4 of the Supplementary Materials exhibits that devices A and B show small radial dependences of at different incident powers for a 0.2 m misalignment away from the drum center.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works on interferometric studies of membrane NMRs demonstrate not only imperfections in the amplitude mode shape [ 51 ], but also variations of with laser beam spot position in the presence of metallic nanoparticles [ 52 ]. A localized laser heating study on membranes made from silicon nitride [ 53 ] suggests that the spot location should be accounted for when performing power-dependent bolometric tests because applying high would induce radial dependence of the measured . Figure S4 of the Supplementary Materials exhibits that devices A and B show small radial dependences of at different incident powers for a 0.2 m misalignment away from the drum center.…”
Section: Resultsmentioning
confidence: 99%
“…More recently quantum cross-correlation technique, probing side band asymmetry, has been employed by Purdy et al to enable temperature measurements up to 300 K [38]. Using free standing silicon nitride (SiN) membranes in high vacuum, Ferreiro-Vila et al [77] have demonstrated room temperature thermometry with 15 µK resolution. At present, the reported uncertainties in optomechanical temperature measurements are of the order of ten percent [38] which is too large for any but niche applications at very low temperatures.…”
Section: Optomechanical Thermometrymentioning
confidence: 99%
“…At cryogenic temperatures it already outperforms traditional stalwarts such as Coulomb Blockade Thermometry [74]. Recent developments have successfully extended the measurement range up to 300 K [38] and demonstrated improved measurement resolution [77]. Further improvements in device design, materials, and measurement 7 Zero-chain traceability refers to the idea of having a top-level temperature realization outside of NMIs.…”
Section: Move Towards Primary Thermometrymentioning
confidence: 99%
“…On this point, cavity optomechanics has become a hot topic in recent years after entering the quantum regime and pushing the limits of signal processing, computing, communication 10 14 , and sensing 15 22 . In most cases, achieving the quantum ground state of the optomechanical resonator necessitates cooling it to nearly absolute zero temperature.…”
Section: Introductionmentioning
confidence: 99%